Post-traumatic (and postsurgical) Guillain-Barré Syndrome: a rare, but treatable entity. Issue 2 (8th February 2021) - Grote, Helen; Sim, Nicholas Keyi; Rinaldi, Simon; Carswell, Christopher
Abstract : Guillain-Barré syndrome (GBS) is an acute, monophasic, polyradiculoneuropathy usually provoked by a preceding infection. The cardinal features are progressive weakness in the upper and lower limbs accompanied by loss of deep tendon reflexes. The diagnosis is made on the basis of the clinical history and examination findings, supported by typical cerebrospinal fluid and electrophysiology findings. Trauma and surgery are well understood but rare precipitants of GBS, which clinicians should be aware of, in order not to miss an opportunity to use immunomodulatory therapies. Furthermore, the presence of postsurgical or post-traumatic GBS should prompt careful assessment for underlying malignancy or autoimmune disease associated with an acute demyelinating polyradiculoneuropathy. Here, we present a case of post-traumatic GBS and discuss the potential mechanisms that might underlie this, as well as the investigations and treatment that should be considered.